Analysis of root-knot nematode early infection events in tomato colonized by the arbuscular mycorrhizal fungus Glomus mosseae - Vos, C.; Elsen, A.; Panis, Bartholomeus; Carpentier, Sebastien C.; Guillier, C.; Dumas-Gaudot, E.; Waele, D. de (International Organisation for Biological Control, 2011)
Arbuscular mycorrhizal fungi (AMF) are obligate root symbionts colonizing the majority of vascular plants on earth. The fungi receive photosynthetic carbon from their host, while the plant benefits from improved water and nutrient uptake, resulting in enhanced growth and survival. In addition, AMF have been shown to reduce the occurrence and impact of several soil pathogens including plant-parasitic nematodes on a wide range of agricultural crops. A wellestablished AMF-colonization is a prerequisite for AMF-induced biocontrol against nematodes, both locally and systemically. Apart from these observations however, the defense mechanisms involved have rarely been investigated for AMF-nematode interactions. Our experiments indicate that the presence of the AMF Glomus mosseae reduces root-knot nematode infection, and already influences the nematode Meloidogyne incognita in its early stage of plant infection. In order to understand the underlying mechanisms of this effect, we are undertaking an in-depth study by monitoring the AMF-plant-nematode interaction during early root-knot nematode infection.